Dilema Hukum dalam Penanganan Pasien Psikotik Berisiko Kekerasan: Studi Kasus dan Perspektif Filsafat Hukum - Bianda Adeti Patriajaya; Muhammad Rifani; Lusiana Pratiwi Sukmajaya; Esa Susanthy Meirianna; Anindya Putri Permatasari; Yuyut Prayuti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article aims to examine the legal and ethical dilemmas in managing psychotic patients who are at risk of committing violence. The research approach used is normative juridical with literature analysis and comparative study. The findings indicate a tension between the protection of patients' human rights and the need for public safety. This study recommends the importance of revising legal policies and strengthening coordination between the health and legal sectors in handling high-risk psychiatric patients.